Peningkatan Pengetahuan Tentang Pijat Oksitosin Pada Ibu Yang Memiliki Bayi Usia 0-6 Bulan Di Desa Rawang Panca Arga Kisaran - Bahri, Serli; Christiani, Meity; Khairinnisa; Diva, Aura (Jurnal Masyarakat Indonesia (Jumas), 2023)
Efforts to increase the provision of breast milk (ASI) have been agreed globally, the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) in the Innocent Declaration and Summit Conference for Children determined that to achieve optimal maternal and child health status, all women You should be able to give only breast milk until the baby is 4 to 6 months old. The breastfeeding problem that mothers often complain about is that the baby often cries or refuses to breastfeed, which then means that there is not enough breast milk. So, the decision was made to stop breastfeeding (Walyani, 2015). A decrease in breast milk (ASI) production in the first days often occurs in post partum mothers. This is caused by a lack of stimulation of the hormones prolactin and oxytocin which play an important role in the smooth production of breast milk (Ulfa 2013). One way that can be done to increase breast milk production is by carrying out breast care or breast care which aims to improve blood circulation and prevent blockage of the milk production ducts, thus facilitating the release of breast milk. Apart from that, there is another way to overcome irregularities in breast milk production, namely oxytocin massage (Purnama, 2013).